Intrinsic Photosensitivity of the Vulnerable Seagrass Phyllospadix iwatensis: Photosystem II Oxygen-Evolving Complex Is Prone to Photoinactivation - Wang, Mengxin; Zhao, Wei; Ma, Mingyu; Zhang, Di; Wen, Yun; Zhong, Mingyu; Luo, Chengying; Hu, Zimin; Zhang, Quansheng (Frontiers in Plant Science, 2022)
Phyllospadix iwatensis, a foundation species of the angiosperm-dominated marine blue carbon ecosystems, has been recognized to be a vulnerable seagrass. Its degradation has previously been reported to be associated with environmental changes and human activities, while there has been little study on its inherent characteristics. In this study, both the physiological and molecular biological data indicated that the oxygen-evolving complex (OEC) of P. iwatensis is prone to photo-inactivation, which exhibits the light-dependent trait. When exposed to laboratory light intensities similar to typical midday conditions, < 10% of the OEC were photo-inactivated, and the remaining active OEC were sufficient to maintain normal photosynthetic activity. Moreover, the photo-inactivated OEC could fully recover within the same day. However, under harsh light conditions, e.g, light intensities that simulate cloudless sunny neap tide days and continual sunny days, the OEC suffered irreversible photo-inactivation, which subsequently resulted in damage to the photosystem II reaction centers and a reduction in the rate of O2 evolution. Furthermore, in situ measurements on a cloudless sunny neap tide day revealed both poor resilience and irreversible photo-inactivation of the OEC. Based on these findings, we postulated that the OEC dysfunction induced by ambient harsh light conditions could be an important inherent reason for the degradation of P. iwatensis.